Hysterangium bonobo: A newly described truffle species that is eaten by bonobos in the Democratic Republic of Congo. (1st November 2020) - Elliott, Todd F.; Georgiev, Alexander V.; Lokasola, Albert Lotana; Smith, Matthew E.
ABSTRACT: Many animals have been shown to eat fungi and most truffle-like fungi depend on animals for spore dispersal via mycophagy. Although these interactions are widespread, they are understudied in many habitats. In this study, we show that bonobos ( Pan paniscus ) forage and feed on an undescribed truffle species in the rainforests of the Democratic Republic of Congo. Based on morphological and molecular assessment of collections, we show that the species eaten by bonobos is a previously undescribed taxon described here as Hysterangium bonobo . This species is known in the local Bantu language (Bongando) as simbokilo and is used for baiting traps to catch several species of small mammals. Our findings highlight the need for further research into mycophagy and systematics of sequestrate fungi in Africa.